2018
DOI: 10.3390/su10103505
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Clay Brick Particles on the Performance of Cement Stabilized Recycled Aggregate as Pavement Base

Abstract: This paper presents an investigation on the influences of clay brick particles on the performance of cement stabilized recycled aggregate as pavement base. The comparative tests of unconfined compressive strength, compressive modulus of resilience, frost resistance, scouring resistance, drying shrinkage and temperature shrinkage of 6 kinds of mixtures with different coarse and fine clay brick particle contents were carried out. Test results showed that the unconfined compressive strength of cement stabilized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Scouring mass loss rate (SML) results representing the anti-scouring property of CSM with RCB at a curing time of 28 d are displayed in Figure 11. It is obvious from the figure that SML values of CSM present an upward tendency with the RCB substitution ratio, as concluded by Miao et al, [49]. The degradation of the anti-scouring property can be mainly attributed to the poor angularity of RCB.…”
Section: Anti-scouring Behaviorsupporting
confidence: 57%
See 1 more Smart Citation
“…Scouring mass loss rate (SML) results representing the anti-scouring property of CSM with RCB at a curing time of 28 d are displayed in Figure 11. It is obvious from the figure that SML values of CSM present an upward tendency with the RCB substitution ratio, as concluded by Miao et al, [49]. The degradation of the anti-scouring property can be mainly attributed to the poor angularity of RCB.…”
Section: Anti-scouring Behaviorsupporting
confidence: 57%
“…Sustainability 2022, 14, 8432 14 of 18 by Miao et al, [49]. The degradation of the anti-scouring property can be mainly attributed to the poor angularity of RCB.…”
Section: Anti-scouring Behaviormentioning
confidence: 99%
“…However, concrete debris is also rising every year and it has been identified as the most created waste from the construction sector [1]. While Malaysia has completed several building projects in the tourist and manufacturing industries and the construction sector continues to be one of the components includes of Malaysia's economy [2], the dumping of construction and demolition debris in landfills has resulted in environmental hazards [3]. According to government sources, Malaysia has a severe shortage of landfill capacity and continuing to dispose of construction and demolition waste at landfills that would jeopardise landfills' strategic use for the disposal of more demanding waste categories.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers used additional materials as aggregates to improve the resilient behavior of the base layer of pavement. It is shown that the addition of coarse clay brick particles has minor impacts on the compressive resilient modulus of the mixture, and it can be significantly increased through the addition of fine particles [29]. Jaffar et al added lime, sand, and marble waste to enhance the mechanical properties of subgrade soil.…”
Section: Introductionmentioning
confidence: 99%